Antibiofilm activities of compounds from natural sources / Muhamad Safwan Razali - Razali, Muhamad Safwan (2021)
In nature, some bacteria have the ability to produce biofilm which acts as a protective barrier against antibiotic killings. When bacteria produce biofilm, they are found to be more resistant against host defense mechanisms as compared to their planktonic counterparts, hence treating biofilm induced infections are known to be more a challenging task. Hence, research have focused on antibiofilm compounds instead as an alternative. The aim of this study was to screen for potential antibiofilm properties from natural sources which include actinomycetes, marine bacteria and frog’s mucus secretion at three different stages of biofilm formation against biofilm producer Staphylococcus epidermidis ATCC 35984 while S. epidermidis ATCC 12228 served as a negative control. A total of 80 bioactive extracts from 40 actinomycetes isolates, 36 bioactive extracts from 18 marine bacterial isolates and nine lyophilized frog mucus secretions were screened for antibiofilm activities. While 31 actinomycetes and 14 marine bacterial isolates displayed very low antibiofilm activity with less than 5% inhibition, no antibiofilm activity was observed in majority of the isolates. In contrast, antibiofilm activities at various stages of biofilm formation was observed in all nine of the frog’s mucus samples. Three samples namely RF1, RF2 and SF2 were able to inhibit the biofilm of S. epidermidis ATCC 35984 at all the three stages of biofilm formation. SF2 was found to display the highest antibiofilm activity at the attachment, maturation and dispersion stages with 97.84 %, 54.50 % and 11.17 % inhibition respectively. Molecular identification of SF2 showed that the nucleotide sequence of this frog was similar to the sequence of haplotype h11 16S ribosomal RNA gene of partial sequence mitochondrial of Fejervarya cancrivora at 100 % similarity. The lyophilized frog’s mucus secretion of F. cancrivora was further fractionated, purified and sequenced to determine the compound responsible for its antibiofilm activities. Thirteen compounds were successfully fractionated. Compound F11 was found to be able to display a very high antibiofilm activity with 96.78% reduction of the biofilm formed by S. epidermidis ATCC35984. Peptide identification of F11 revealed that the major amino acid sequences, AAPNGLYFGG was found to be similar to the sequence of bacteriocin (Hypothetical protein M446_0103) from Methylobacterium species at 67 % similarity. This research shows that frogs mucus has a good potential as antibiofilm agent and should be further explored for their maximum capacity.